PENGEMBANGAN USAHA KULINER â€œWAROENG MAKAN TEPI LAUTâ€ DI KAWASAN MEGA MAS, KOTA MANADO - Angraini ., Datunsolang; Jenny Baroleh; Benu Olfie L.S. (AGRI-SOSIOEKONOMI, 2016)
This study aims to describe how the development of a culinary efforts and make an assessment as the basis to determine the culinary business development. This study began in March until June 2016. This research located in "Waroeng Makan Tepi Laut", Kawasan Mega Mas, Kota Manado. The data collected in this research included primary data and secondary data. The primary data obtained from interviews with managers, managers and employees. And also interview based questionnaire on the visitors / customers as many as 15 people. Secondary data was collected from the Office of Administration â€œWaroeng Makan Tepi Lautâ€. The results of this study indicate that â€œWaroeng Makan Tepi Lautâ€ has a strategic business location, the menu selection is varied, the prices offered can be affordable, quality service owned â€œWaroeng Makan Tepi Lautâ€ is quite good, has a typical menu favored by the customers / visitors, ample parking location and stage music favored by the customers / visitors.